Pengaruh Perencanaan Pajak, Keputusan Pendanaan Dan Pertumbuhan Perusahaan Terhadap Nilai Perusahan - Shella Maulana Putri; Adhitya Putri Pratiwi (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This study aims to provide evidence and analyze the effect of tax planning, funding decisions, and company growth on firm value. The research method used is descriptive research analysis with a quantitative approach and through secondary data. The population in this study came from consumer cyclical companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2022. The sampling technique used the Purposive sampling method to produce a sample of 17 companies which were analyzed for 5 years of observation, the sample obtained was 85 data. The data is processed using E-views 10 software. The data analysis technique in this research is Panel Data Regression Analysis. The results showed (1) Tax planning, funding decisions, and company growth simultaneously affect firm value, (2) Tax planning has no significant and negative effect on firm value, (3) Funding decisions have a significant and positive effect on firm value, (4) Company growth has no significant and negative effect on firm value.